Integrating metaheuristic optimization algorithms with random forest to predict waste generation in construction and demolition projects - Awad, Ruba; Budayan, Cenk; Calik, Idil; Gurgun, Asli Pelin; Koc, Kerim (ELSEVIER, 2026)
The construction sector is a significant source of global waste, making accurate and proactive prediction of Construction and Demolition Waste (C&DW) essential for sustainable resource management and circular economy efforts. However, estimating C&DW at the project level remains a major challenge. This paper investigates whether C&DW prediction accuracy can be enhanced by integrating the Random Forest (RF) model with two metaheuristic optimization algorithms: the Archimedes Optimization Algorithm (AOA) and Grey Wolf Optimization (GWO). Based on data from 200 real-world projects in Palestine, the GWO-RF model achieved the highest predictive accuracy using only four input variables: project type, start date, building type, and number of floors. To ensure model transparency, Shapley Additive Explanations (SHAP) analysis confirmed that project type and the number of floors were the most influential parameters. This study thus provides a practical, robust, and highly accurate model to support effective waste management strategies in the construction industry.
Keywords: Construction and demolition waste; Waste generation; Archimedes optimization algorithm; Grey wolf optimization; Random Forest; Gaza-Palestine; SHAP analysis; MANAGEMENT; MODEL; QUANTIFICATION; BUILDINGS; OPTIONS; Construction & Building Technology; Engineering